"I Don't Think Anorexia Is the Way Out": Reconstruction of Meaning in Women's Narratives of Anorexia Nervosa over 10 Years. Issue 2 (2nd April 2016) - Conti, Janet E.
Abstract : This article explores how a group of nine Australian women who identified their past or present experiences as anorexia nervosa ascribed meaning to their experiences and negotiated their identities longitudinally over 10 years. A critical discursive analysis of their narratives found anorexia to be a troubled, socially constructed category. Within the discursive context of talk not confined to the dominant vocabulary of illness, the women negotiated and, over time, renegotiated alternative ways of speaking to depict their experiences, including through use of metaphor and a lexicon of values. The findings challenge health professionals to take greater accountability for the problematic effects of speaking only in the dominant medical paradigm and to recognize the transformative potential of privileging the voices of people who experience anorexia nervosa, including prioritizing their terms and engaging with their values.